DESAIN WEB PT. ANDALAS MULTIMEDIA PROMOSINDO - GITA PRIMA DONA, Dini Faisal, S.Ds., M.Ds. San Ahdi, S.Sn., M.Ds. (DEKAVE : Jurnal Desain Komunikasi Visual, 2018)
Andalas Mutimedia Promosindo merupakan is one of bussines entity in advertising (Outdoor & Indoor Promotion) and event organizer, that located in Padang city exactly in kalawi street no. 25 Padang. In the beginning, this company engage in the Event Organizer, but as time be run out, this company also served some of graphic design services and digital printing. Therefore tight of competition between, so it needed a new visual media of comunication and can draw attention to audience, is promotion by use media website. Choosen this media is available with needed of Andalas Multimedia Promosindo company.Method of designing web design of Andalas Multimedia Promosindo this company, in basicly by not optimally view of web design yet and information that complete from the company. Method that using is 5W+1H approach that made as basic concept of problem solution is what, who, where, when, why, and how and how so, this approached being method that effectife and comunicatif.The first, media that using at web design of Andalas Multimedia Promosindo company is website media. Then supporting media that uses is web banner, poster promotion card, sticker, t-shirt, totebag,and name card.Keyword : Web design, Website, Promotion